Wavelet analysis of quadriceps power spectra and amplitude under varying levels of contraction intensity and velocity. Issue 5 (16th September 2014) - Croce, Ronald; Miller, John; Chamberlin, Kent; Filipovic, David; Smith, Wayne
ABSTRACT Introduction: We investigated the effect of contraction intensity [100%, 75%, 50%, and 25% maximum voluntary contraction (MVC)] and movement velocity (50°, 100°, 200°, and 400°/s) on surface electromyography root mean square amplitude (SEMGRMS) and median frequency (SEMGMDF) of rectus femoris (RF), vastus lateralis (VL), and vastus medialis (VM). Methods: SEMGs during knee extension were resolved into their respective frequencies using wavelet transformations. Results: RF, VL, and VM muscles displayed increased SEMGMDF as contraction intensity increased from 25% to 50% MVC and from 75% to 100% MVC, and each muscle displayed its own unique frequency shifting patterns. The SEMGMDF was not influenced by movement velocity. SEMGRMS increased in all 3 muscles as contraction intensity increased and was influenced by movement velocity, with the highest values observed at 400° and 200°/s. Conclusions: We infer that increasing contraction intensity facilitates greater recruitment of fast‐twitch muscle fibers, but there are differing responses in RF, VL, and VM muscles. Muscle Nerve50: 844–853, 2014